Validation of baseline information of reproductive health & disease control programme - Afsana, Kaosar; Mahmud, Shah Noor (BRAC Research and Evaluation Division (RED), 2019)
The Reproductive Health and Disease Control (RHDC) programme has been in operation since 1996. This study was conducted in RHDC programme areas to validate the accuracy of baseline information as collected by the programme. Selected process indicators, such as use of antenatal care, assistance during delivery by the trained personnel, contraceptive prevalence rate and continuation and discontinuation rate of methods were chosen to compare data between the programme and survey. For use of antenatal care and trained personnel during delivery, a sample of210 women who gave birth during January-December 1996 was drawn from among the members of village organisations (VOs). For contraception, 450 currently married women were randomly selected from the same VOs. The validated data of the programme were found in close agreement with the survey data. For use of antenatal care, 99% of the programme data were found to be accurate. Of the women who received assistance during delivery, 91 °u were confirmed by survey. Accuracy was validated in 95% of cases for contraceptive prevalence. Continuation rate of methods during 1996 as validated by the survey was 83% and discontinuation rate 23%. Predictive value of use of antenatal care, use of trained personnel and contraceptive prevalence is very high but in contrast that of discontinuty of methods is very poor. It has been suggested that due to very high accuracy rate of programme data, it can be used as a reliable source of information. However, validation of programme data can be done from time to time to check its accuracy. Moreover, record-keeping system should be well-maintained and SSs' activities well-supervised.